(untitled) (World Bulletin of Social Sciences, 2023)
The most common natural hazards in mountainous areas are earthquakes, mudflows, landslides, landslides, and snow avalanches. For the steppe regions, hurricanes, storms and tornadoes, snow drifts are most characteristic